2016
DOI: 10.1080/02755947.2016.1214646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consumption‐Oriented versus Trophy‐Oriented Fisheries on Muskellunge Population Size Structure in Northern Wisconsin

Abstract: To determine whether a consumption‐oriented fishery was compatible with a trophy‐oriented fishery for Muskellunge Esox masquinongy, we modeled effects of a spearing fishery and recreational angling fishery on population size structure (i.e., numbers of fish ≥ 102, 114, and 127 cm) in northern Wisconsin. An individual‐based simulation model was used to quantify the effect of harvest mortality at currently observed levels of recreational angling and tribal spearing fishery exploitation, along with simulated incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…() predicted that trophy opportunities would increase under more conservative regulations. Furthermore, Faust and Hansen () indicated that management for trophy potential may not be possible in fisheries exhibiting high exploitation rates.…”
Section: Discussionmentioning
confidence: 99%
“…() predicted that trophy opportunities would increase under more conservative regulations. Furthermore, Faust and Hansen () indicated that management for trophy potential may not be possible in fisheries exhibiting high exploitation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating individual fish age is an important component of fisheries science and fish ecology because age data are used to understand growth, mortality, recruitment, and life history (Paloheimo 1980;Catalano and Allen 2010;Vitale et al 2019). Subsequently, age data are used to monitor fish populations (Pine et al 2001;Switzer et al 2015) and to evaluate implemented (Maceina et al 1998;Oliver et al 2021) or simulated (Faust and Hansen 2016;Bauerlien et al 2022) management actions. To estimate age, daily or annual increments (i.e., annuli) in the calcified structures of fish are counted.…”
Section: Introductionmentioning
confidence: 99%
“…Even with increased angler participation, Muskellunge harvest rates are low and release rates are estimated to be greater than 97% (Fayram 2003; Margenau and Petchenik 2004; Kerr 2007; Landsman et al 2011; Simonson 2012; Richards 2017). Because of the Muskellunge's life history characteristics (low population density and long life span) and historical exploitation, small increases in mortality rates can affect abundance and size structure (Faust and Hansen 2016). Therefore, research identifying the factors that influence mortality and resultant population‐level effects is important to management agencies and angling groups (Arlinghaus et al 2007).…”
Section: Introductionmentioning
confidence: 99%